Accumulation of cadmium in growing peanut (Arachis hypogaea L.) seedlings - its effect on lipid peroxidation and on the antioxidative enzymes catalase and gualacol peroxidase - Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Journal of Plant Nutrition and Soil Science, 2008)
In plants exposed to high metal concentrations, mechanisms to counteract the oxidative burst are crucial for its survival. To investigate the temporal sequence of physiological reactions of peanut seedlings (Arachis hypogaea L.) to cadmium exposure, seeds were cultured in increasing concentrations of CdCl(2), ranging from 50 to 300 mu M. Germination frequency was scored, and the distributions of Cd in root, stem, and leaves were determined after 2 and 4 weeks of culture. Lipid peroxidation and activities of antioxidative enzymes including catalase (CAT, EC 1.11.1.6) and guaiacol peroxiclase (GPX; EC 1.11.1.7) were estimated in these three parts of the plant. Germination of seedlings was not affected, but the growth of seedlings was severely suppressed with increasing concentrations of CdCl(2) and incubation period. Pattern of Cd distribution in the three organs varied with concentration and period of exposure to Cd. Increased lipid peroxidation was detected in all parts of the developing seedlings with increasing metal accumulation. Catalase and guaiacol peroxidase activity varied in the three parts of the seedlings with concentration of Cd and incubation period. Guaiacol peroxidase activity appears to be more active in scavenging the reactive oxygen species in developing peanut seedlings. The results of the present experiment demonstrate the advantages of a tissue-culture model system in studying the complex network of interactions of various factors in stress tolerance.
Keywords: Abiotic stress; heavy metal; stress tolerance; TBARS; thiobarbituric acid; Tissue culture

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Rashmi, Deo; Barvkar, Vitthal T.; Nadaf, Altafhusain B.; Kadoo, Narendra Y. (Journal of Plant Biochemistry and Biotechnology, 2025)
Salinity poses a formidable challenge to agriculture, detrimentally impacting plant growth and the yield of several crops globally. Pandanus odorifer (Forssk.) Kuntze is a highly salt-stress resilient plant that grows naturally along the coastal regions of Asia, Southeast Asia, and Polynesia. It is frequently found as a frontier species along the sandy shores receiving constant salt sprays. MicroRNAs (miRNAs) play essential regulatory roles in growth, development, and combating various biotic and abiotic stresses. Thus, characterizing miRNAs and their targets is critical to understanding their roles in salt stress tolerance. Through a rigorous analysis based on homology, secondary structure and signatures of other miRNA genes, we identified 52 conserved nonredundant miRNAs from the P. odorifer transcriptome data. These miRNAs were diverse and belonged to 23 miRNA phylogenetic families. Several miRNAs, including pod-MIR156a, pod-MIR164d, and pod-MIR535d, demonstrated distinct expression patterns in response to salt stress. Their target genes exhibited opposing expression trends, corroborating the intricate miRNA-target relationship. Delving deeper into their influence, we discovered that these miRNAs mainly targeted transcription factors that are known for their pivotal roles in stress responses. We also detected four miRNA-star (miRNA*) sequences (the complementary strands of functional mature miRNAs), which supports the authenticity of the identified miRNAs. This study unveils the intricate regulatory mechanism through which miRNAs may reinforce salt stress tolerance in P. odorifer, providing a promising avenue for enhancing crop resilience to various stresses through miRNA-based strategies.
Keywords: Abiotic stress; microRNA; miRNA targets; Salinity tolerance; salt stress; Transcription factors